Thrombocytopenia in Older Adults - McMahon, Brandon J.; Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2014)
Thrombocytopenia in older patients is associated with several characteristics that are often underrecognized. Among them are the risk of bleeding complications, the senescence of the bone marrow, the increased use of multiple drugs, and greater comorbidity. In this article, the various forms of thrombocytopenia, including primary and drug-associated immune thrombocytopenias, as well as other drug-associated thrombocytopenias, are reviewed. In addition, how age-related changes in platelet function may affect the bleeding risk is discussed.
Keywords: thrombocytopenia; older adults; bleeding; immune thrombocytopenic purpura; drug-induced thrombocytopenia